2018
DOI: 10.1093/botlinnean/boy043
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the extensive hybridization in South American Nothofagus through karyotype analysis

Abstract: Extensive phylogeographic and population studies in Nothofagus revealed that hybridization, introgression and plastid capture are common phenomena that have occurred throughout the evolutionary history of the genus. Here, detailed karyotypes of ten South American Nothofagus spp. were constructed using chromosome fluorescent banding with the aim of (1) investigating if karyotype features were compatible with the formation of fertile interspecific hybrids, particularly when growing in sympatry and (2) identifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…We hypothesize that woody species are also slower than herbaceous plants to generate and fix rearranged chromosomes or altered chromosome numbers. Karyotyping of multiple species within the same genus has been conducted in several genera of woody plants, including Pinus (Hizume et al, 2002), Nothofagus (Acosta and Premoli, 2018) and Eucalyptus (Ribeiro et al, 2016). Intriguingly, all these studies demonstrated a highly similar karyotype among different species in the same genus.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that woody species are also slower than herbaceous plants to generate and fix rearranged chromosomes or altered chromosome numbers. Karyotyping of multiple species within the same genus has been conducted in several genera of woody plants, including Pinus (Hizume et al, 2002), Nothofagus (Acosta and Premoli, 2018) and Eucalyptus (Ribeiro et al, 2016). Intriguingly, all these studies demonstrated a highly similar karyotype among different species in the same genus.…”
Section: Discussionmentioning
confidence: 99%
“…Cycles of hybridization-introgression and chloroplast capture among extant and ancestral taxa result in concordant cpDNA phylogeographic patterns, whereas nuclear DNA (ITS) illustrates relationships among delimited species (Acosta & Premoli, 2010). In addition, karyotype conservation can contribute to explaining the existence of extensive “plastid capture” that has been observed in wood taxa (sensu: Acosta & Premoli, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The same phenomenon is found within New Zealand species, where the hybridization occurs among them; this has been recorded by Poole (1951) and Poole (1958). In addition, hybridizations have been recorded in cultivation out of natural habitat range for distinct Nothofagus species of different continental distribution but always among the same subgenus, that suggests a strong degree of intrinsic reproductive isolation among the different subgenus (Heenan & Smissen, 2013; Acosta & Premoli, 2018). For subgenus Nothofagus , the natural hybridization process which has been confirmed for the three evergreen species (Donoso & Atienza, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies recognise adaptive introgression as bene cial for species tness (Acosta and Premoli, 2018, Aeschbacher et al 2017, Hohmann and Koch, 2017, Horn et al 2018, Lehnert et al 2019, Ma et al 2019, Paun et al 2016, Semenov et al 2018. Possible reasons for the bene t of introgression are the potential of adaptive introgression for promoting individual survival (Hejase andLiu, 2016, Norris et al 2015), range expansion (Whitney et al 2015), species divergence (Morales et al 2017), evolutionary rescue (Quigley et al 2019) and adaptive radiation (Poelstra et al 2018, Zhang et al 2016.…”
Section: Introductionmentioning
confidence: 99%